Impact of consumption profile discontinuities on the feasibility of a PV plant. (August 2018) - Pasini, G.; Ferrari, L.; Desideri, U.; Reboa, R.; Ghirlanda, C.
Abstract: The revenues of a grid-connected photovoltaic plant are strongly related to the local climatic conditions. In addition, since self-consumed electricity is much more valuable than that traded with the main power grid, also consumption profile plays a key role in the profitability of a PV system. Self-consumption to total PV production ratio depends on the temporal mismatch between energy generation and demand. The amount of energy that is not self-consumed may be very high in the case of a consumption profile with several discontinuities. This study is focused on the analysis of a grid-connected PV system serving a compressed natural gas (CNG) fueling station. These facilities are energy-intensive users, characterized by high variability of electricity demand due to intermittent operation of gas compressors: in a few seconds the total load may change from 100% to 5% and vice versa very frequently during the day. The analysis was based on data acquired on the field for the compression station and those already present in the literature for solar irradiation. The influence on plant design of the time step used for the analysis was studied in detail. The outcomes showed that the typical and well-assessed design approaches of a PV pant may lead to errors when used for the design of systems with several consumption profile discontinuities.